DETERMINANTS OF OPPO SMARTPHONE PURCHASE DECISION MAKING AMONG STUDENTS (CASE STUDY OF GUNADARMA KARAWACI STUDENTS) - Rizki Muti Agustiani; Risa Septiani; M. Haidir Rahmat Homza (International Journal Multidisciplinary Science, 2023)
This study aims to analyze the effect of product quality, price and brand image on purchasing decisions on Oppo smartphones partially and simultaneously. Respondents in this study were 100 respondents, the sampling technique used was purposive sampling technique using the Slovin formula. The data collection method uses an online questionnaire. The data analysis technique used is multiple linear regression analysis test, t test, classic assumption test, coefficient of determination test, f test using SPSS 20 for windows. The results of this study indicate that partially product quality and brand image have an effect on purchasing decisions, while price has no effect. Simultaneously product quality, price and brand image have a significant effect on purchasing decisions with a determination coefficient of 65% influenced by these three variables, namely product quality, price and brand image, and the rest are influenced by variables outside the research